2012
DOI: 10.1177/1091581812465969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Toxicity of Intravenous Delivery of Auroshell Particles (Gold–Silica Nanoshells)

Abstract: Gold nanoshells (155 nm in diameter with a coating of polyethylene glycol 5000) were evaluated for preclinical biocompatibility, toxicity, and biodistribution as part of a program to develop an injectable device for use in the photothermal ablation of tumors. The evaluation started with a complete good laboratory practice (GLP) compliant International Organization for Standardization (ISO)-10993 biocompatibility program, including cytotoxicity, pyrogenicity (US Pharmacopeia [USP] method in the rabbit), genotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
157
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(162 citation statements)
references
References 30 publications
5
157
0
Order By: Relevance
“…10 Phase II clinical trials have been announced (http:// www.cytimmune.com/user/register#pipeline). 11 Several other gold-chemotherapy agents, such as Auroshell 12,13 and Aurimune, are under clinical trials or seeking approval. 9,10,[12][13][14] Noteworthy, at the beginning of 2013, the international pharmaceutical company AstraZeneca in partnership with CytImmune focused on developing a cancer nanomedicine based on AuNPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Phase II clinical trials have been announced (http:// www.cytimmune.com/user/register#pipeline). 11 Several other gold-chemotherapy agents, such as Auroshell 12,13 and Aurimune, are under clinical trials or seeking approval. 9,10,[12][13][14] Noteworthy, at the beginning of 2013, the international pharmaceutical company AstraZeneca in partnership with CytImmune focused on developing a cancer nanomedicine based on AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…11 Several other gold-chemotherapy agents, such as Auroshell 12,13 and Aurimune, are under clinical trials or seeking approval. 9,10,[12][13][14] Noteworthy, at the beginning of 2013, the international pharmaceutical company AstraZeneca in partnership with CytImmune focused on developing a cancer nanomedicine based on AuNPs. 15 The successful application of AuNPs as tools for cancer treatment is mainly associated to their unique physicochemical properties and acceptable biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, the NSs aggregated into coarse particles cannot be passively distributed to other organs. This result means that the local injection of NSs might overcome the cytotoxicity problem which is caused by the uncontrollable circulation of nanoparticles, such as after intravenous injection [18][19][20]. …”
Section: Identification Of the Migration Of Macrophages Into Tumor Xementioning
confidence: 99%
“…A second GNP clinical trial plans to use AuroShell® particles (Nano-spectra Biosciences Inc, Houston, TX) administered intravenously, followed by exposure to an 808 nm laser as photothermal ablation therapy for the treatment of head and neck cancer [7]. In vivo data from the same study demonstrated that the 155 nm nanoshells capped with 5000 M w PEG have the ability to accumulate at the tumour site in canines with brain tumours; human trials are ongoing as of September 2014.…”
Section: Gold Nanoparticlesmentioning
confidence: 91%